2007
DOI: 10.1167/iovs.06-0426
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variations in the Relationship between Macular Thickness Measurements and Myopia

Abstract: Retinal thickness is related to refractive error/axial length in normal subjects with regional variations in correlation within the 6-mm macular region. Analysis of macular thickness in the evaluation of macular diseases and glaucoma should be interpreted only in the context of refractive errors and the location of measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
195
2
13

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(250 citation statements)
references
References 20 publications
34
195
2
13
Order By: Relevance
“…This suggests the influence of axial length over macular thickness in myopia. This correlates with the study done by Lam et al, in which minimum foveal thickness increased with axial length [14][15][16][17][18][19]. Similarly, Hwang et al, [20] also found that in healthy young myopic eyes showed thinner macular thickness, lower macular volume and thicker foveal thickness were associated with longer axial length.…”
Section: Discusionsupporting
confidence: 85%
See 1 more Smart Citation
“…This suggests the influence of axial length over macular thickness in myopia. This correlates with the study done by Lam et al, in which minimum foveal thickness increased with axial length [14][15][16][17][18][19]. Similarly, Hwang et al, [20] also found that in healthy young myopic eyes showed thinner macular thickness, lower macular volume and thicker foveal thickness were associated with longer axial length.…”
Section: Discusionsupporting
confidence: 85%
“…Thus the increase in the foveal thickening with increasing degree of myopia can be an early sign of vitreoretinal traction. This incomplete vitreous traction in the myopic eyes may be associated with retinal detachment, myopic traction maculopathy and foveoschisis [14]. Springer and Hendrickson have explained the reason for increased foveal thickness in experimental animal models.…”
Section: Discusionmentioning
confidence: 99%
“…[22][23][24] Lam et al 25 used TD OCT with higher axial scanning resolution and sampling density, and demonstrated that there were regional variations of retinal thickness within the macular region that correlated with axial length. The outer ring macular thickness was found to be reduced with longer axial length, while the inner ring macular thickness increased with axial length.…”
Section: Retinamentioning
confidence: 99%
“…yapmış oldukları son dönem çalışmada, 80 yüksek miyop (SE< -6,00 D), 37 düşük-orta miyop (SE -0,50 ile -6,00 D arasında), 26 kontrol grubu olmak üzere toplam 143 olguyu üç gruba ayırarak incelemişlerdir. 22 Stratus OKT kullanarak elde edilen total ortalama fovea, minimum fovea, iç ve dış makula kalınlığı değerleri bu üç grup arasında karşı-laştırılmıştır. Minimum fovea ve ortalama fovea kalınlıklarını yüksek miyoplarda anlamlı şekilde daha büyük ve dış makular kalınlığı yüksek miyoplarda diğer iki gruba göre anlamlı olarak daha düşük bulmuşlardır.…”
Section: Gereç Ve Yöntemlerunclassified
“…Dış makular kalınlık ve total ortalama makular kalınlık ile AU arasında negatif korelasyon söz konusudur. 22 Lam ve ark.nın yapmış oldukları çalışma sonuçları çalışmamızın bulgularını destekler nitelikteydi. 22 Fakat çalışmamızda dış makular kalınlık ve total ortalama makular kalınlık değerleri ile AU/SE arasında zayıf korelasyon vardı.…”
Section: Gereç Ve Yöntemlerunclassified